2007
DOI: 10.1016/j.peptides.2006.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of NPY compounds with the rat glucocorticoid-induced receptor (GIR) reveals similarity to the NPY–Y2 receptor

Abstract: The rat glucocorticoid induced receptor (rGIR) is an orphan G protein-coupled receptor awaiting pharmacological characterization. Among known receptors, rGIR exhibits highest sequence similarity to the Neuropeptide Y (NPY) -Y 2 receptor (38-40%). The pharmacological profile of rGIR was investigated using 125 I-PYY 3-36 , a Y 2 -preferring radioligand and several NPY analogs. rGIR displayed a similar displacement profile as reported for the Y 2 receptor, in that the Y 2 -selective C terminus fragments of NPY an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 31 publications
0
31
1
Order By: Relevance
“…One caveat to this conclusion is the lack of a demonstrable difference in the efficiency of Foxp3 acquisition by naïve T cells in vivo in the absence or presence of GPR83, whereas it was suggested by others that GPR83 may facilitate the acquisition of Foxp3 expression (12). Although we cannot exclude the possibility that under certain conditions GPR83 signaling may be absolutely necessary, our results suggest that in vivo endogenous GPR83 plays a redundant role in the induction of Foxp3 expression in peripheral T cells, perhaps due to signals provided by other receptors, such as neuropeptide Y receptor 2, able to compensate for GPR83 deficiency (21). Moreover, it is possible that the discrepancy between our results and those of the study by Buer and coauthors is due to the reliance of the latter on the overexpression of GPR83 in naïve Foxp3 Ϫ T cells, which normally express GPR83 at low levels in both resting and activated states.…”
Section: Discussioncontrasting
confidence: 56%
“…One caveat to this conclusion is the lack of a demonstrable difference in the efficiency of Foxp3 acquisition by naïve T cells in vivo in the absence or presence of GPR83, whereas it was suggested by others that GPR83 may facilitate the acquisition of Foxp3 expression (12). Although we cannot exclude the possibility that under certain conditions GPR83 signaling may be absolutely necessary, our results suggest that in vivo endogenous GPR83 plays a redundant role in the induction of Foxp3 expression in peripheral T cells, perhaps due to signals provided by other receptors, such as neuropeptide Y receptor 2, able to compensate for GPR83 deficiency (21). Moreover, it is possible that the discrepancy between our results and those of the study by Buer and coauthors is due to the reliance of the latter on the overexpression of GPR83 in naïve Foxp3 Ϫ T cells, which normally express GPR83 at low levels in both resting and activated states.…”
Section: Discussioncontrasting
confidence: 56%
“…4, C and D); thus, the HA tag did not appear to affect binding. A study examining rGPR83 reported binding of NPY (23). However, we found that NPY at concentrations below 1 μM did not displace [ 125 I]Tyr-rPEN and exhibited only a small (~20%) and not significant (one-way ANOVA; P = 0.37, F 7,40 = 1.109) displacement with 10 μM NPY (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although GPR83 is currently referred to as an “orphan” GPCR, indicating that its ligand has not been definitively established, a report in 2007 claimed that NPY was a ligand for this receptor (23). We found that radiolabeled PEN binding to GPR83 was not affected by NPY concentrations below 1 μM, although 10 μM NPY caused a partial, nonsignificant, displacement of PEN binding.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular profiling showed that POA WSN express Y2 as well as the GPR83, an orphan receptor sharing homology to Y2 and found by one group to interact with NPY in vitro (Sah et al, 2007; Eberwine and Bartfai, 2011; Dubins et al, 2012). Interestingly, downregulation of GPR83 expression in the POA by shRNA was recently shown to reduce CBT (discussed below; Dubins et al, 2012).…”
Section: Hypothalamic Orexigenic and Anorexigenic Peptidesmentioning
confidence: 99%